FINANCIAL ECONOMIC IMPACT OF TAX STANDARDS COMPLIANCE IN CORPORATE MANAGEMENT - Alva Suárez, Karina Esther (2017)
In relation to the Income Tax Law, it mentions that the expenses that are causal for the generation of taxable income, which must meet certain formal and substantial requirements, are deductible. However, there is the problem that companies lose the right to deduct their expenses and other tax benefits, because they do not have control policies and procedures, as well as training, which impacts on their economic and financial management. The present work is developed through descriptive studies (observation of the facts) and correlational studies (measurement of the degree of relationship that exists between the variables). The method used is inductive, since it is the study of a case. Determining that non-compliance with tax rules due to a lack of control procedures and policies; as well as the lack of training of the members of the organization negatively impacts the economic (profitability) and financial (liquidity) results of the organization.